PEMODELAN SISTEM SERVIS SEPEDA MOTOR PADA CV. BERKAT RR ABADI BEKASI - SUGIYONO - (STIKOM CKI, 2019)
CV. Berkat RR Abadi Motor was established 2010 because at the time there was nobike shop around the house is located in Perumnas Rawa-Lumbu-Bekasi, I engaged in the service of motor services and sales of spare parts. Spare parts sales system that existed at CV. Independent Motor today still run manually thus making the authors are interested in creating a system that is more computerized and structured by program application and the Design System by UML modeling. CV. Berkat RR Abadi Motor is a business entity engaged in official Motorbike services that provide maintenance, repair and sales of spare parts. In every business activity always has a problem, such as having problems in the vehicle repair system and spare parts sales. This system was designed to help the process of controlling the motor spare parts stock and assist the process of administration and create sales reports. This system which will facilitate the sales process and control of spare parts, so as to give a stock report more accurate motor spare parts. And minimize the possibility of fraud because the stock is more unsupervised motor spareparts